(untitled) (International journal of artificial intelligence, 2026)
This article presents a comprehensive comparative analysis of the water spirit archetype as manifested in English and Uzbek classical folklore. Drawing upon mythological, symbolic, and functional frameworks, the study examines the typological parallels and divergences between water spirit figures in the oral traditions of two culturally distinct literary heritages. The English folklore tradition, encompassing figures such as mermaids, water nymphs, kelpies, and Jenny Greenteeth, is compared with Uzbek folk narratives featuring the Suv parisi (water fairy), Suv ayoli (water woman), and related aquatic supernatural beings. Through the application of Jungian archetypal theory, Propp’s morphological analysis, and the Aarne–Thompson–Uther (ATU) motif index, this study identifies shared archetypal patterns rooted in universal human responses to water as a liminal element, while simultaneously highlighting the culturally specific moral, didactic, and cosmological functions these figures serve within their respective traditions. The findings reveal that despite geographical and cultural distance, both traditions employ water spirit figures as mediators between the human and supernatural worlds, as embodiments of feminine power and danger, and as narrative devices for enforcing social norms. However, the Uzbek tradition demonstrates a stronger integration with Islamic cosmology and Central Asian shamanic heritage, whereas English water spirits reflect pre-Christian Celtic and Germanic mythological substrata. This comparative analysis contributes to the broader field of cross-cultural folklore studies and offers insights into the universal and particular dimensions